2022
DOI: 10.22540/jfsf-07-047
|View full text |Cite
|
Sign up to set email alerts
|

Otago Exercise Program Delivery using Digital Practice: A Prospective Case Report

Abstract: Activity restrictions during the COVID-19 pandemic left many older adults without access to community-based falls prevention programs. Despite a lack of evidence to support the digital delivery of exercise and rehabilitation, these services were quickly implemented during the pandemic in an effort to prevent the transmission of COVID-19, yet support a continuity of care. Our report describes the novel practice and digital delivery of a condensed Otago Exercise Program, a well-documented falls prevention progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Likewise, there were significant changes in the STST test in 1 min with an average of two repetitions at the end of the program, similar to those obtained in other studies that used this test in teleprehabilitation programs developed during the pandemic 31,32 . For FSTST, a recent study performed remote home‐based program during the pandemic using digital technology and also achieved significant improvements in run times for this test 33 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Likewise, there were significant changes in the STST test in 1 min with an average of two repetitions at the end of the program, similar to those obtained in other studies that used this test in teleprehabilitation programs developed during the pandemic 31,32 . For FSTST, a recent study performed remote home‐based program during the pandemic using digital technology and also achieved significant improvements in run times for this test 33 …”
Section: Discussionsupporting
confidence: 82%
“…31,32 For FSTST, a recent study performed remote home-based program during the pandemic using digital technology and also achieved significant improvements in run times for this test. 33 In terms of feasibility, this study demonstrated a high recruitment rate (99%), with a moderate retention rate of (53%), good patient satisfaction, and no adverse events were reported during teleprehabilitation. Despite the fact that prehabilitation seems to convey positive benefits on physical functioning, the short surgical waiting times represented the main obstacle to implement the telerehabilitation program in CRC surgery candidates, as reported by other studies.…”
Section: Discussionmentioning
confidence: 68%